Disrupted development from head to tail: Pervasive effects of postnatal restricted resources on neurobiological, behavioral, and morphometric outcomes - Kent, Molly H.; Jacob, Joanna C.; Bowen, Gabby; Bhalerao, Janhavi; Desinor, Stephanie; Vavra, Dylan; Leserve, Danielle; Ott, Kelly R.; Angeles, Benjamin; Martis, Michael; Sciandra, Katherine; Gillenwater, Katherine; et al. (Frontiers in Behavioral Neuroscience, 2022)
When a maternal rat nurtures her pups, she relies on adequate resources to provide optimal care for her offspring. Accordingly, limited environmental resources may result in atypical maternal care, disrupting various developmental outcomes. In the current study, maternal Long-Evans rats were randomly assigned to either a standard resource (SR) group, provided with 4 cups of bedding and 2 paper towels for nesting material or a limited resource (LR) group, provided with a quarter of the bedding and nesting material provided for the SR group. Offspring were monitored at various developmental phases throughout the study. After weaning, pups were housed in same-sex dyads in environments with standard resources for continued observations. Subsequent behavioral tests revealed a sex x resource interaction in play behavior on PND 28; specifically, LR reduced play attacks in males while LR increased play attacks in females. A sex x resource interaction was also observed in anxiety-related responses in the open field task with an increase in thigmotaxis in LR females and, in the social interaction task, females exhibited more external rears oriented away from the social target. Focusing on morphological variables, tail length measurements of LR males and females were shorter on PND 9, 16, and 21; however, differences in tail length were no longer present at PND 35. Following the behavioral assessments, animals were perfused at 56 days of age and subsequent immunohistochemical assays indicated increased glucocorticoid receptors in the lateral habenula of LR offspring and higher c-Fos immunoreactivity in the basolateral amygdala of SR offspring. Further, when tail vertebrae and tail tendons were assessed via micro-CT and hydroxyproline assays, results indicated increased trabecular separation, decreased bone volume fraction, and decreased connectivity density in bones, along with reduced collagen concentration in tendons in the LR animals. In sum, although the restricted resources only persisted for a brief duration, the effects appear to be far-reaching and pervasive in this early life stress animal model.